2006
DOI: 10.1111/j.1468-2338.2006.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising the dynamics of employee information and consultation: evidence from the Republic of Ireland

Abstract: The debate concerning the emerging regulatory environment for employee voice continues apace, in particular the requirements to inform and consult employees as a result of the European Employee Information and Consultation Directive. This article examines the processes used to inform and consult employees across 15 case studies in the Republic of Ireland. It evaluates different voice arrangements using a conceptual framework that seeks to capture the dynamics of different employee voice schemes across union an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 27 publications
(47 reference statements)
2
52
0
3
Order By: Relevance
“…Dundon et al (2003) similarly found that employees were much more likely than mangers to express misgivings about the scope and depth of information and consultation at their workplaces; they found Irish organisations to be significantly better at informing rather than consulting employees.…”
Section: Voluntary Failure?mentioning
confidence: 90%
See 4 more Smart Citations
“…Dundon et al (2003) similarly found that employees were much more likely than mangers to express misgivings about the scope and depth of information and consultation at their workplaces; they found Irish organisations to be significantly better at informing rather than consulting employees.…”
Section: Voluntary Failure?mentioning
confidence: 90%
“…It is dealing with the challenges of managing change that has to a large extent driven the contemporary focus on employee involvement and partnership. However, the literature consistently shows that existing voice and participation arrangements, be they under the rubric of partnership (NCPP, 2004) or otherwise seem to be considerably more effective in dealing with incremental as opposed to transformative change (Dundon et al, 2003). It seems the more fundamental in nature the change facing the organisation, the less "say" workers are granted; in such situations, information tends to significantly predominate over consultation (ibid, p. 54).…”
Section: One Of the Main Reasons The Directive Is Likely To Have Suchmentioning
confidence: 99%
See 3 more Smart Citations